1987
DOI: 10.1135/cccc19872589
|View full text |Cite
|
Sign up to set email alerts
|

Micellar enzymology: Potentialities in applied areas (biotechnology)

Abstract: Micellar enzymology, a new trend in molecular biology, studies the catalysis by enzymes entrapped into hydrated reversed micelles of surfactants (detergents, phospholipids) in organic solvents. The effect of solubilization on enzymatic properties is briefly considered. Applications of such biocatalytic systems in fine organic syntheses, in clinical and chemical analyses, and in medicine, as well as probable future trends in biotechnology are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Furthermore, the possibility of increasing concentration of both enzyme and substrate is also improved at the enhanced interfacial region [14] (Scheme 1), probably because of alteration in partition coefficients. [6,9,22] As it was found that the lipase activity is larger in series II surfactants (4)(5)(6) relative to corresponding surfactants of series I and III, we can explain this from the present study exclusively on the basis of the head-group area ( Table 1). Although the differences in A min value did not appear to be significant in some cases, it is probably sufficient enough to affect the enzyme activity.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Furthermore, the possibility of increasing concentration of both enzyme and substrate is also improved at the enhanced interfacial region [14] (Scheme 1), probably because of alteration in partition coefficients. [6,9,22] As it was found that the lipase activity is larger in series II surfactants (4)(5)(6) relative to corresponding surfactants of series I and III, we can explain this from the present study exclusively on the basis of the head-group area ( Table 1). Although the differences in A min value did not appear to be significant in some cases, it is probably sufficient enough to affect the enzyme activity.…”
Section: Resultsmentioning
confidence: 55%
“…[1][2][3][4] Lipases, a class of surface-active enzymes, [1] are widely exploited in diverse transformations in w/o microemulsions. [1,[5][6][7] The catalytic efficiencies of these enzymes are believed to be dependent primarily on the local concentrations of water and other ions present in the vicinity of the enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard the fact that uricase is concentrated within a microbody, which also contains a potential Oz-generating mechanism (catalase; Hanks et al 1981), should not be overlooked. Furthermore, the kinetic properties of many enzymes have been shown to be markedly altered through their confinement at high concentration in lipophyllic micellar structures (Martinek et al 1987) which might be likened, to some extent, to microbodies. The enzyme has been successfully puri-fled from nodules of a number of ureide-forming species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…When surfactants assemble in oil , the aggregate is referred to as a reverse micelle. In a reverse micelle, the hydrophilic heads of the surfactants are in the core of the micelle and the hydrophobic tails maintain favorable contact with oil [6][7][8]. The most commonly used surfactants are thiols, oleic acid, laurate salts.…”
mentioning
confidence: 99%